1992
DOI: 10.1037/h0079335
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric status of women presenting for infertility evaluation.

Abstract: Psychiatric symptomatology, incidence of clinical depression, measures of self-esteem, and sexual functioning were not found to be significantly different between a group of 118 women undergoing infertility evaluation and treatment and a demographically similar group of 83 routine-care women patients with no known fertility problems. However, a significant number of the infertility patients reported changes in mood and in sense of self-worth since becoming concerned about conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 23 publications
0
24
0
6
Order By: Relevance
“…Mit zunehmender Dauer entwickelt sich für viele Paare daraus eine schwere Lebenskrise (vgl. [47,27,8,13,15,53]). Da sich die Hoffnungen monatlich auf das Ausbleiben der Menstruation konzentrieren, besteht die emotionale Erfahrung der Sterilität aus zyklischen Wechselbädern zwischen Hoffnung, Versagensangst, Frustration und Niedergeschlagenheit [27].…”
Section: Schlüsselwörterunclassified
“…Mit zunehmender Dauer entwickelt sich für viele Paare daraus eine schwere Lebenskrise (vgl. [47,27,8,13,15,53]). Da sich die Hoffnungen monatlich auf das Ausbleiben der Menstruation konzentrieren, besteht die emotionale Erfahrung der Sterilität aus zyklischen Wechselbädern zwischen Hoffnung, Versagensangst, Frustration und Niedergeschlagenheit [27].…”
Section: Schlüsselwörterunclassified
“…Two separate studies conducted by Cwikel et al and Domar et al reported a twofold increased prevalence of depressive emotions in infertile women compared to childbearing women. The prevalence of major depressive disorder was estimated as 11% in infertile women compared to 3.9% in normal female population in a study by Downet and colleagues in 1992 (7)(8)(9). Other studies have been conducted to measure depression, hostility, and anxiety scores in infertile women, demonstrating dramatically higher scores in infertile women than those in a matched fertile population.…”
Section: Introductionmentioning
confidence: 99%
“…Medical definitions typically further distinguish between primary and secondary infertility. Some research makes the primary/secondary distinction based on conceiving versus not conceiving prior to experiencing infertility (Downey & McKinney, 1992;Larsen, 2000;Vahidi et al, 2009); other research makes the primary/secondary distinction based on the birth of a child (Epstein & Rosenberg, 2005;Nene et al, 2005;Awartani et al, 2009). In this article, we examine the effects of different primary/secondary distinctions on fertility-specific distress (FSD) and infertility help-seeking among a probability-based sample of US women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Medical dictionaries define secondary infertility as 'infertility in a patient who has previously conceived' (Anderson, 2003, p. 923), and most clinicians and reproductive endocrinologists accept this definition. Some researchers of psychosocial implications of infertility have followed their lead (Downey & McKinney, 1992;Larsen, 2000;Vahidi et al, 2009). Other researchers (Epstein & Rosenberg, 2005;Nene et al, 2005;Awartani et al, 2009) define secondary infertility as infertility in a woman who has had at least one previous child.…”
Section: Introductionmentioning
confidence: 99%